Advances in microRNA from adipose-derived mesenchymal stem cell-derived exosome: focusing on wound healing. Issue 46 (18th November 2022) - Ma, Jiahui; Yong, Ling; Lei, Pengyu; Li, Hua; Fang, Yimeng; Wang, Lei; Chen, Haojie; Zhou, Qi; Wu, Wei; Jin, Libo; Sun, Da; Zhang, Xingxing
Abstract : ADMSC-Exo-miRNAs as therapeutic strategies for wound healing. Abstract : Skin wounds are a common condition causing economic burden and they represent an urgent clinical need, especially chronic wounds. Numerous studies have been conducted on the applications of stem cell therapy in wound healing, with adipose-derived mesenchymal stem cells (ADMSCs) playing a major role since they can be isolated easily, yielding a high number of cells, the less invasive harvesting required, the longer life span and no ethical issues. However, the lack of standardized doses and protocols, the heterogeneity of clinical trials, as well as the incompatibility of the immune system limit its application. Recent studies have demonstrated that specific stem cell functions depend on paracrine factors, including extracellular vesicles, in which microRNAs in exosomes (Exo-miRNAs) are essential in controlling their functions. This paper describes the application and mechanism whereby ADMSC-Exo-miRNA regulates wound healing. ADMSC-Exo-miRNA is involved in various stages in wounds, including modulating the immune response and inflammation, accelerating skin cell proliferation and epithelialization, promoting vascular repair, and regulating collagen remodeling thereby reducing scar formation. In summary, this acellular therapy based on ADMSC-Exo-miRNA has considerable clinical potential, and provides reference values for developing new treatment strategies for wound healing.